ANALISIS IMPLEMENTASI TUJUAN DAN CAPAIAN PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR PADA SDN 193 MANDALAN - Nur Laila; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the implementation of learning objectives and achievements in Indonesian Language teaching under the Merdeka Curriculum at SDN 193 Mandalan, Makassar, using a qualitative descriptive approach on grade 4 teachers, students, and learning documents through observation, interviews, and document analysis. Findings reveal that teachers have developed Learning Objective Pathways (ATP) and teaching modules based on Learning Achievement Standards (CP), yet objective formulations remain general, diagnostic assessments are suboptimal, and digital literacy is hindered by limited facilities. Implementation shows positive progress but requires advanced teacher training and facility improvements to achieve integrated literacy competencies (listening, speaking, reading, writing).​